2011
DOI: 10.1093/jac/dkr137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial stewardship in critical care: a systematic review

Abstract: More rigorous research is needed, but available evidence suggests that antimicrobial stewardship is associated with improved antimicrobial utilization in the intensive care unit, with corresponding improvements in antimicrobial resistance and adverse events, and without compromise of short-term clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
242
1
29

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(279 citation statements)
references
References 36 publications
7
242
1
29
Order By: Relevance
“…9,13,30,[156][157][158][159] Yet little has been written on the relevance of such interventions for doctors who are still undergoing training but are already required to make antimicrobial prescribing decisions in the clinical setting (for an example, see Brennan and Mattick 36 ). Given the widely recognised importance of social dynamics in driving prescribing behaviours, 34,35 the role of doctors in training deserves explicit attention, as they often need to manage power and teamwork dynamics along with their learning and career progression, in ways different from their senior colleagues.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…9,13,30,[156][157][158][159] Yet little has been written on the relevance of such interventions for doctors who are still undergoing training but are already required to make antimicrobial prescribing decisions in the clinical setting (for an example, see Brennan and Mattick 36 ). Given the widely recognised importance of social dynamics in driving prescribing behaviours, 34,35 the role of doctors in training deserves explicit attention, as they often need to manage power and teamwork dynamics along with their learning and career progression, in ways different from their senior colleagues.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Nursing management started this soon after the study hospital had opened in response to a growing awareness of the need to manage ICU environments optimally, and provide safe care for patients. [4] Small community hospitals use antimicrobial therapy more frequently than large academic medical centres and are less likely to have AMS program mes in the acute-care setting. [11] The early detection of pathogens, appropriate use of antibiotics and reduction of healthcare-associated infections are essential in the care of the critically ill patient, and all ICUs should have AMS programmes that aim to ensure prompt, effective treatment.…”
Section: Organisational Rolementioning
confidence: 99%
“…This is especially important in an ICU, which has the highest proportion of patients vulnerable to infection and uses the most antibiotics in the hospital setting. [4] Research into the prevalence of infection in private and public ICUs in South Africa (SA) found that, in the private ICU sector, an inappropriate antibiotic was prescribed in 60.8% of patients, duration of administering an antibiotic was inappropriate in 81.7% of patients, and de-escalation was used in only 19.7% of patients. The authors attributed these figures to poor prescribing practices in this sector.…”
mentioning
confidence: 99%
“…Bununla birlikte, bazı CLSI sınır değerlerinin EUCAST sınır değerle-rinden farklı olduğu göz önüne alındığında, güncel epidemiyolojik verilerin eskileriyle karşılaştırılmasında hangi antibiyotiklerde değişik-lik bekleneceği bilinmeli, antibiyotiklere direnç artışı izlenirken bu konu göz önünde tutulmalı-dır. Doğru antibiyotik kullanımının direnç artışı-nı azaltacağı yapılan çalışmalarla kanıtlanmıştır (3) . Ülkemizin EUCAST standartlarına geçtiği bu dönemde iki rehber arasındaki direnç oranların-daki farklılıkların belirlenmesine gereksinim vardır.…”
Section: Introductionunclassified